2016
DOI: 10.1108/ijshe-07-2014-0105
|View full text |Cite
|
Sign up to set email alerts
|

International field experiences promote professional development for sustainability leaders

Abstract: Purpose – This paper aims to describe, explain and evaluate a graduate education program that provides international project experiences and builds competencies related to collaborative problem-solving, cultural capacity to work globally and sustainable development. Design/methodology/approach – Qualitative analysis of survey data from 28 students supplemented by observation and interviews conducted before, during and after a multi-week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 29 publications
0
29
0
2
Order By: Relevance
“…Accordingly, there have been calls for new kinds of education for sustainability, as evidenced by the United Nations’ Decade of Education for Sustainability (2005-2015), and the tertiary education sector has been the hub of research in this area (see e.g., Barth et al, 2007; Sipos, Battisti, & Grimm, 2008; Sterling, 2011; Svanström et al, 2008). The education for sustainability literature reports of various pedagogical approaches designed to develop the knowledge, skills, and values required by sustainability leaders, including active and problem-based learning (MacVaugh & Norton, 2012); authentic problems, learning cycles, shared inquiry, transdisciplinarity, exploration, and engagement (Hull, Kimmel, Robertson, & Mortimer, 2016); and encouraging critical and reflective thinking about sustainability paradigms (Stubbs & Cocklin, 2008). While these and other similar contributions emphasize the importance of personal values for sustainability, this approach has also been challenged by those who believe that universities are not the place for the “moral agenda” (Butcher, 2007).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Accordingly, there have been calls for new kinds of education for sustainability, as evidenced by the United Nations’ Decade of Education for Sustainability (2005-2015), and the tertiary education sector has been the hub of research in this area (see e.g., Barth et al, 2007; Sipos, Battisti, & Grimm, 2008; Sterling, 2011; Svanström et al, 2008). The education for sustainability literature reports of various pedagogical approaches designed to develop the knowledge, skills, and values required by sustainability leaders, including active and problem-based learning (MacVaugh & Norton, 2012); authentic problems, learning cycles, shared inquiry, transdisciplinarity, exploration, and engagement (Hull, Kimmel, Robertson, & Mortimer, 2016); and encouraging critical and reflective thinking about sustainability paradigms (Stubbs & Cocklin, 2008). While these and other similar contributions emphasize the importance of personal values for sustainability, this approach has also been challenged by those who believe that universities are not the place for the “moral agenda” (Butcher, 2007).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Specifically, participants in international service-learning report a greater appreciation for cultural differences, including how to recognise and navigate differences while maintaining respect for the other (Hull et al 2016). For example a nationally representative sample in the U.S. found that individuals who participated in servicelearning were more likely to have interacted and socialised with someone from a different ethnic group in the previous year, compared to non-service-learning peers (Martin et al 2006).…”
Section: Diversity Competencementioning
confidence: 99%
“…Individuals engaging in international service-learning frequently report an increased awareness of their own strengths and weaknesses (Hull et al 2016). Research related to volunteering and role identity suggests that volunteering is intertwined with personal development (Grube & Piliavin 2000).…”
Section: Identity Developmentmentioning
confidence: 99%
“…Por decorrência, apresentar uma simplificação sistêmica usando a teoria dos grafos de modo a medir a conectividade dentro da matriz curricular. Propondo simplificações e integração com eixos como a Sustentabilidade (Hull, Kimmel, Robertson, & Mortimer, 2016).…”
Section: Introductionunclassified
“…Muitas matérias não são sistêmicas e se comunicam com as outras, integrando o conhecimento desejado. Em fez de fazer uma pesquisa qualitativa de depois quantitativa, na forma tradicional da metodologia (Hull et al, 2016). Esta pesquisa propôs um modelo, de forma a atender ao currículo de Engenharia de Produção em qualquer lugar do mundo.…”
Section: Introductionunclassified